(untitled) (Journal of Engineering, 2023)
Soil improvement has developed as a realistic solution for enhancing soil properties so that structures can be constructed to meet project engineering requirements due to the limited availability of construction land in urban centers. The jet grouting method for soil improvement is a novel geotechnical alternative for problematic soils for which conventional foundation designs cannot provide acceptable and lasting solutions. The paper’s methodology was based on constructing pile models using a low-pressure injection laboratory setup built and made locally to simulate the operation of field equipment. The setup design was based on previous research that systematically conducted unconfined compression testing (U.C.Ts.). The soil improvement techniques were investigated by injecting a low-pressure mixture of water and ordinary Portland cement (O.P.C.) with (0.8, 1, and 1.3) W/C ratios. The study revealed the relationship between pile model samples (U.C.Ts.) and W/C ratios. It also showed that the pile model samples’ (U.C.Ts.) result decreased from 14 to 12 to 10 MPa, respectively, with an increase in W/C ratios from 0.8 to 1 and 1.3, respectively. Furthermore, the stiffness characteristics of a jet grouting column were calculated based on Mohr’s Circles theory, and numerous theoretical approaches obtained the consequences of tensile strength.